PENGEMBANGAN POLYCLINIC MOBILE APPLICATION UNTUK MENINGKATKAN PELAYANAN KESEHATAN PADA MASYARAKAT PEKERJA - Setiyadi, Andi; Wuryanto, Endro Dwi (Universitas PGRI Semarang, 2021)
The use of mobile devices is increasingly popular. Mobile devices are increasingly equipped with advanced hardware and software technology. With dynamic performance and practical on mobile devices can master the development of the world ICT industry (information and communication technology). Software has become one of the spearheads of mobile success device. The creation of application programs is an important breakthrough in mobile development device. Likewise, the development of the Polyclinic Mobile Application in lecturer research This beginner is to provide solutions to problems that exist at the polyclinic at environment of PT. Eka Sandang Duta Prima Semarang, which is not yet supported by ICT, so in providing health services to the community, workers who are less than optimal can resolved. In developing the Polyclinic Mobile Application, it is not only a registration feature only, but there are several other features that were developed such as; polyclinic profile, schedule practice, modern queuing system, recording medical records, view patient history, take notes medical action, noting the drug administered.